Proceedings of the 5th International Conference on Mechanical Engineering, 26-28 December 2003, Dhaka, Bangladesh - International Conference on Mechanical Engineering (5th : 2003 : Dhaka, Bangladesh) (Dhaka, Bangladesh : Bangladesh University of Engineering and Technology, 2003)
18